CRIME VICTIMS’ RIGHT TO COMPENSATION IN BANGLADESH: A COMPARATIVE APPROACH - Fhameda Qudder (European Scientific Journal, ESJ, 2015)
The true dictum of criminal justice system is to ensure justice for victim. But the whole criminal justice system of Bangladesh is planned in such a way that an accused can acquire fair trial and justice. As far as victim is concerned, common belief is that, trial and conviction of an accused can adequately redress the injury suffered by victim. Therefore they do not have the right get compensation. Nevertheless, State is supposed to ensure a better deal to the victims of crime to make the proceeding equally fair to both sides. Considering the importance of victims’ right to compensation this write up beginning focuses on the development of victims’ right to compensation, as well as justification for the same. Subsequently stating the existing compensation scheme within the current criminal justice system, the write proceed to discuss a comparative picture between other states and Bangladesh.